Effect of antiamyloid-β drugs on Alzheimer's disease: study protocol for a systematic review and meta-analysis. Issue 5 (18th May 2021) - Lyu, Diyang; Shi, Yuqing; Lyu, Xuanxin
Abstract : Introduction: Alzheimer's disease (AD) is a neurodegenerative disease with a complex aetiology involving multiple targets and pathways. With the continuous growth of the ageing population, the burden of AD is increasing year by year. However, there has not been new drug approved for over a decade. In addition, the efficacy of memantine and cholinesterase inhibitors is not satisfactory. As amyloid-β (Aβ) is regarded as the core pathological change and the trigger mechanism of AD, anti-Aβ therapy may be an effective therapy. In recent years, a lot of clinical trials have been carried out in this field, but the results have not been well summarised and analysed. Methods and analysis: In this study, we will study the effect of anti-Aβ antibodies versus placebo on the clinical efficacy, biomarkers, neuroimaging and safety in different stages of AD, as well as the factors that may affect the efficacy. Drugs that only target the existing Aβ are regarded as anti-Aβ antibodies. Following electronic databases will be searched from inception to April 2021: Medline-Ovid, EMBase-Ovid, Cochrane Central and clinical trial registration platform ClinicalTrials.gov. After identifying eligible studies through screening title, abstract and read full text of each retrieved literature, we will contact the correspondence authors for additional information and grey literatures. To get more reliable results, random effect model will be conducted for meta-analysis and analysis of subgroups or subsets. Funnel plot, Egger's test and sensitivity analysis will be conducted to explore potential heterogeneity. Meta-regression will be conducted to identify the factors that may affect clinical efficacy. Evidence quality assessment and trial sequential analysis will be conducted to assess the quality of evidence and confirm the reliability of the results in this study. Ethics and discussion: This study does not require formal ethical approval. The findings will be submitted to a peer-review journal. PROSPERO registration number: CRD42020202370.